The healthy life. - Silva, A C; Luz, A; Medeiros, A; Macedo, E (Acta Médica Portuguesa, 1997)
This study is based on a comparison of the habits and opinions of a group of pupils on entering the Damaia Preparatory School (5th and 6th years of education) and of the same group on leaving this School. Its aim is to contribute towards an adequate education for health at school in order to promote healthy living habits. The study was based on the comparison of data obtained from two random samples, chosen from the same group of pupils when entering (n1 = 36 out of a total of 368) and leaving (n2 = 32 out of a total of 164) the above mentioned school. The collection of data was carried out by means of a multiple-choice questionnaire given to a total of 532 pupils. The results demonstrated that the frequencies have changed in the following way: a) bathing has increased; b) tea drinking has decreased; c) the image of the teacher as a smoker has become less frequent; d) the number of pupils who have tried alcoholic beverages has increased; e) mother’s smoking habits have increased. The other trends that were found in the study showed that there were no significant changes in either the behaviour or opinions that had been studied.